Oligopoly and outsourcing - Subhayu Bandyopadhyay; Howard J. Wall (Institute for the Study of Labor (IZA), 2005)
With outsourcing comes a perceived tension between the competitive pressures faced by domestic firms and the effect that outsourcing has on domestic workers. To address this tension, we present a general-equilibrium model with an oligopolistic export sector and a competitive import-competing sector. When there is a minimum wage, an outsourcing tax might be desirable and the usual profit-shifting objectives of an export subsidy are mitigated, perhaps completely, because it might lead to higher unemployment. Also, increased international competition has no affect on the level of outsourcing, but the direction of its effect on unemployment and national income depends on the relative factor intensities of the two sectors. Under wage flexibility, an outsourcing tax cannot be justified and the profit-shifting motive is the same as in a model without outsourcing. Further, if export subsidies are not possible due to WTO regulations, it is optimal to subsidize rather than to tax outsourcing. Finally, the effect of increased foreign competition on welfare depends on the relative factor intensities of the two sectors.
Keywords: 330; outsourcing; oligopoly; minimum wage; Outsourcing; Oligopol; Internationaler Wettbewerb; Allgemeines Gleichgewicht; Steuerwirkung; Mindestlohn; Exportsubvention; Wohlfahrtseffekt; Theorie